Adaption of Artificial Intelligence (AI) to enhance business and collaboration between countries, focusing on Saudi Arabia - Zafar, Nisar Ahmed (Journal of Accounting, Business and Management (JABM), 2024)
Artificial Intelligence (AI) is one of the most ingenious inventions drastically transforming the business world. The question is whether the current growth of AI is all hype or if it has the potential to revolutionize the world is raised by the abundance of intelligent goods and services that have emerged in recent times. Technological developments in AI pave the way for creating technologies that resemble humans and can operate independently and imitate our intellectual processes. Numerous industries have shown considerable interest and enthusiasm in adopting AI due to technological advancements. As a result, numerous businesses are making significant investments to leverage this opportunity through innovative business models based on AI. The study aims to establish a model based on an evidence-synthesis approach that demonstrates how the business sector in Saudi Arabia can incorporate AI to achieve better outcomes and strengthen its relationships with other countries. However, the study also highlights some advantages and disadvantages of adopting AI models in the business industry so a balanced approach can be used to incorporate AI in different aspects of the business. The study recommends incorporating AI in different health, education, and business sectors in Saudi Arabia to foster international relationships in Saudi Arabia.